2019
DOI: 10.1186/s10194-019-1062-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, burden, and clinical management of migraine in China, Japan, and South Korea: a comprehensive review of the literature

Abstract: BackgroundThe objective of this review was to determine the unmet needs for migraine in East Asian adults and children.MethodsWe searched MEDLINE and EMBASE (January 1, 1988 to January 14, 2019). Studies reporting the prevalence, humanistic and economic burden, and clinical management of migraine in China (including Hong Kong and Taiwan), Japan, and South Korea were included. Studies conducted before 1988 (before the International Headache Society [IHS] first edition of the International Classification of Head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 65 publications
3
72
1
Order By: Relevance
“…One strength of this study was the use of a validated instrument WPAI to quantify the work impairment among migraine patients in comparison to the nonmigraine population in Japan, as few other studies have used validated tools for work impairment assessment [9][10][11][12][13][14]. Also, previous studies have primarily focused on analyzing HRU and costs related to migraine within the migraine population [37,38]; hence, our study provided a novel point of view in the burden of the healthcare system utilization and costs of migraine in comparison with the non-migraine population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One strength of this study was the use of a validated instrument WPAI to quantify the work impairment among migraine patients in comparison to the nonmigraine population in Japan, as few other studies have used validated tools for work impairment assessment [9][10][11][12][13][14]. Also, previous studies have primarily focused on analyzing HRU and costs related to migraine within the migraine population [37,38]; hence, our study provided a novel point of view in the burden of the healthcare system utilization and costs of migraine in comparison with the non-migraine population.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying differences, especially the difference in the prevalence of migraine across the regions should be noted when comparing across regions. The prevalence was reported to be around 6% to 8% in Japan [9,11], 15% in Europe [41,42] and in the US [43]. A recent literature review revealed that there was a low level of disease awareness and use of prescription medication for migraine in East Asia [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine is a common PHD, which constitutes a major financial and social burden 130,131 . It is proper that we resort to relatively harmless and efficacious interventions for its successful management.…”
Section: Discussionmentioning
confidence: 99%
“…Headaches are one of the most frequent complaints in medicine in general and a frequent disorder in the working population that significantly affects absenteeism and loss of productivity; however, its effect on work efficiency has been insufficiently studied [1][2][3]. Some primary headaches are commonly linked with a broad range of psychiatric comorbidities [4].…”
Section: Introductionmentioning
confidence: 99%